ANALISIS PELAKSANAAN ZAKAT PROFESI: UPAYA PENGENTASAN KEMISKINAN DI KOTA MEDAN - Siti Mujiatun (Universitas Islam Negeri Sumatera Utara, 2016)
The public and private institutions of Medan, Bank Sumut, PT Telkom and UMSU implement the Zakat based on the Leader’s Policy. The research method using descriptive qualitative, interviews, documentation, observation. The results showed the Zakat Profession is done by deducted 2.5% of monthly salarySOP; 1) Decision Letter from Management, 2). Socialization, 3). 2.5% per monthly, 4), Mustahiq, 5). Evaluation. The obstacles; 1). lack of professional, 2), Muzaki is less trustful, 3). Direct distribution of alms to the recipients. 4). Lack of trust to the Institute. (5). No punishment refuse alms collection. 6). Lack of socialization 7). Paper-based, instead of IT management, 8). Khilafiyah, 9). No regulation of the profession Zakat, Recommendation; 1). All institutions of Medan should collect profession alms and distribute it productively. 2) Government and DPRD of Medan should formulate and issue local regulation on profession alms.